Green Cosmetic Purchase Intention: The Impact of Green Brands Positioning, Attitude, and Knowledge - Dwi Lestari, Diyah; Roostika, Ratna (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2022)
Energy crisis and the increasing environment problem have led people to be aware of green sustainable product nowadays. It has given a birth to the idea of green cosmetic which shifted from synthetic cosmetic of providing skincare needs. With these conditions, green cosmetic has seen as an important element, and yet should be investigated. This research included four variables such as Green Brand Positioning, Green Brand Attitude, Green Brand Knowledge, and Green Cosmetic Purchase Intention. Furthermore, the total of 180 valid data from respondents in the range of 18- >40 years old was gathered in this research. The result indicated 3 variables (Green Brand Positioning, Green Brand Attitude, and Green Brand Knowledge) had positive influence on Green Cosmetic Purchase Intention. Moreover, Green Brand Knowledge has positive influence on Green Brand Attitude which it is significantly mediated the relationship between Green Brand Knowledge and Green Cosmetic Purchase Intention. The population of this study is Indonesian with experience in buying green cosmetic product. More specifically, are those who have shopped green cosmetic. The sampling technique used is online questionnaires using Google Form. There were 200 respondents valid questionnaires returned and further analyzed using Structural Equation Modeling method with AMOS. The results show significant influence of Green Brand Positioning, Attitude and Knowledge to Green Cosmetic Purchase Intention. Green Brand Attitude is also a significant mediating variables between green brand knowledge and green cosmetic purchase intention.